Words, Names, Nature, Earth: On the Poetry of Pierre-Albert Jourdan - Yves Bonnefoy (Studies in 20th & 21st Century Literature, 1989)
An ambivalence toward language is present throughout the work of Pierre-Albert Jourdan. Words are associated with the closure of a grey world; they are always arriving late, after the fact; they are veils, masks, dreams detached from truth, knowledge, and immediacy. Yet, words and names hold out the possibility of hope; they can designate the presence of beauty in the world; they can mediate the encounter of self and other. The human word signifies itself through the substance of the world and the communion of beings. At the intersection of natural reality—the center of the real for Jourdan—and of language are found the garden, the earth, places of an ephemeral, haiku like presence where the natural opens itself to the human.
Keywords: Pierre-Albert Jourdan; words; ambivalence; closure; veils; dreams; truth; knowledge; hope; beauty; self; other; sign; signifier; real; reality; garden; earth